2017
DOI: 10.1364/oe.25.030388
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown flash at telecom wavelengths in InGaAs avalanche photodiodes

Abstract: Quantum key distribution (QKD) at telecom wavelengths (1260 - 1625 nm) has the potential for fast deployment due to existing optical fibre infrastructure and mature telecom technologies. At these wavelengths, Indium Gallium Arsenide (InGaAs) avalanche photodiode (APD) based detectors are the preferred choice for photon detection. Similar to their Silicon counterparts used at shorter wavelengths, they exhibit fluorescence from recombination of electron-hole pairs generated in the avalanche breakdown process. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The presence of a significant backflash radiation has been experimentally demonstrated in both commercially available InGaAs/InP [36] and Si-based [28] SPADs. In the case of an InGaAs-based SPAD with a nominal detection efficiency of about 10%, the backflash emission can be a source of significant information leakage, thus compromising the security of the entire QKD system [37], [38]. An experiment with a silicon-based detector also revealed a considerable rate of backflash emission.…”
Section: Spad Incident Photons Backflash Photonsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a significant backflash radiation has been experimentally demonstrated in both commercially available InGaAs/InP [36] and Si-based [28] SPADs. In the case of an InGaAs-based SPAD with a nominal detection efficiency of about 10%, the backflash emission can be a source of significant information leakage, thus compromising the security of the entire QKD system [37], [38]. An experiment with a silicon-based detector also revealed a considerable rate of backflash emission.…”
Section: Spad Incident Photons Backflash Photonsmentioning
confidence: 99%
“…This explains why different SPAD models operating in different regimes exhibit different backflash spectral distribution, temporal profile, and intensity. Although there exists an analytical theory of backflash radiation, this effect has been mainly investigated experimentally for QKD applications, and the reported results are tied to the properties of the concrete SPADs used [28], [35], [37], [38].…”
Section: Pbsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note, however, that characterizing the spectrum of the backflashes is also important for enforcing this point in order to more accurately determine the information leakage. While this has been partially explored in previous studies, [18][19][20] these have not corrected for the spectral response of the measurement apparatus. We believe that this is an important avenue for future work, not only from a security perspective but also to shed light on the precise origin of backflashes within APDs.…”
Section: Article Scitationorg/journal/aplmentioning
confidence: 99%
“…It has been shown that APDs are susceptible to emitting light after detection, known as backflashes. [17][18][19][20][21] Backflashes can then allow Eve to act in a more passive way and thus ascertain which of Bob's detectors has clicked without having to interact with any components in the QKD system. However, no studies have yet been performed on fast-gated detectors that are used in stateof-the-art QKD systems.…”
mentioning
confidence: 99%